Suicide Bereavement and Postvention: Advances in Research, Practice and Policy - Andriessen, Karl; Krysinska, Karolina; Levi-Belz, Yossi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Experiencing the suicide of a close person is often a major life event, which increases the risk of maladaptive grief reactions, social, physical, and mental health problems, and suicidal behavior in the bereaved individuals. However, people bereaved by suicide may also experience long-term positive outcomes regarding personal or post-traumatic growth. The field of suicide bereavement research is evolving rapidly. Hence, this reprint is particularly focused the advance knowledge on bereavement and postvention. In this reprint, you can find papers that enhance our understanding of grief after suicide and how to help those who are bereaved, including studies on suicide grief in specific populations and studies on interventions and support offered to the bereaved or their social environment, in addition studies based on novel methods and studies that contribute to the development of theory or models. We believe that this reprint can add important knowledge on our journey to help suicide-loss survivors in their continued struggle with the loss on their loved ones to suicide.